2013
DOI: 10.1113/expphysiol.2012.068338
|View full text |Cite
|
Sign up to set email alerts
|

The Nlrp3 inflammasome promotes myocardial dysfunction in structural cardiomyopathy through interleukin‐1β

Abstract: New findings r What is the central question of this study?Heart failure is associated with persistent sterile inflammation that worsens disease severity; however, the molecular mechanisms behind cytokine recruitment and their relevance in the diseased myocardium remain unknown. r What is the main finding and its importance?We show that interleukin-1β is activated downstream of the Nlrp3 inflammasome in calcineurin-transgene-induced structural heart disease. Genetic deletion of Nlrp3 abrogated inflammasome sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
123
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(127 citation statements)
references
References 37 publications
4
123
0
Order By: Relevance
“…These studies are consistent with findings of mitochondrial dysfunction and increased organellar fission in brain samples of autistic individuals [79]. Similar involvement of NLRP3-associated inflammation is found in Alzheimer's disease [80] and cardiomyopathy [81]. These associations strongly suggest that inflammation and mitochondria comprise a pathogenic axis that is likely to play a role in a wide range of prominent human diseases.…”
Section: Inflammatory Damage To Mitochondriasupporting
confidence: 77%
“…These studies are consistent with findings of mitochondrial dysfunction and increased organellar fission in brain samples of autistic individuals [79]. Similar involvement of NLRP3-associated inflammation is found in Alzheimer's disease [80] and cardiomyopathy [81]. These associations strongly suggest that inflammation and mitochondria comprise a pathogenic axis that is likely to play a role in a wide range of prominent human diseases.…”
Section: Inflammatory Damage To Mitochondriasupporting
confidence: 77%
“…Thus, calcineurin appears to be one of the important calciumregulated proteins that modulate the expression of pro-IL-1␤. Further evidence supporting the relevance of this pathway comes from a recent report demonstrating that calcineurin overexpression in cardiac myocytes also leads to enhanced IL-1␤ release with activation of the NLRP3 inflammasome (30).…”
Section: Discussionmentioning
confidence: 97%
“…Several recent studies have also revealed the association of the Q705K polymorphism in the NLRP3 gene (rs35829419) with various inflammatory diseases including celiac disease (9), diabetes type-1 (8), abdominal aortic aneurysms (14), Crohn's disease (15) and rheumatoid arthritis (10 CARD8 (C10X) genes was found to be associated with rheumatoid arthritis (10) and Crohn's disease (15,16). Considering a possible key role of the NLRP3 inflammasome in promoting myocardial inflammation (17) and athero sclerosis through the production of pro-inflammatory cytokine IL-1β (18), the aim of the present study was to investigate the effect of Q705K polymorphism in NLRP3 gene and the risk of developing MI in a northern Swedish population.…”
Section: Introductionmentioning
confidence: 99%